2017
DOI: 10.4085/1062-6050-52.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Bone Marrow Lesion Volume and Knee Pain Within 4 Weeks After Anterior Cruciate Ligament Injury

Abstract: Context: After an anterior cruciate ligament (ACL) injury, a majority of patients have a traumatic bone marrow lesion (BML, or bone bruise). The clinical relevance of posttraumatic lesions remains unclear.Objective: To explore the cross-sectional associations between traumatic BML volume and self-reported knee pain and symptoms among individuals within 4 weeks of ACL injury.Design: Cross-sectional exploratory analysis of a randomized clinical trial.Setting: Orthopaedic departments at 2 hospitals in Sweden. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…This is low in comparison to most other studies that report between 69% and 100% [4,6,8,11,29,43,46,50]. As with the overall frequency of BMLs, the frequency of BMLs in the lateral femur and tibia were lower in this study, 44% and 39%, compared to the majority of studies reporting over 60% for the lateral femur and over 70% for the lateral tibia [4,6,11,23,24,29,43,46,50]. This diference is likely driven by the inclusion of ACL-injured subjects regardless of treatment and age.…”
Section: Discussioncontrasting
confidence: 82%
“…This is low in comparison to most other studies that report between 69% and 100% [4,6,8,11,29,43,46,50]. As with the overall frequency of BMLs, the frequency of BMLs in the lateral femur and tibia were lower in this study, 44% and 39%, compared to the majority of studies reporting over 60% for the lateral femur and over 70% for the lateral tibia [4,6,11,23,24,29,43,46,50]. This diference is likely driven by the inclusion of ACL-injured subjects regardless of treatment and age.…”
Section: Discussioncontrasting
confidence: 82%
“…This could be due to the fact that initial lateral plateau tissue damage from trauma might have been the strongest factor in OA initiation/progression in participants with post-traumatic OA and KAM during gait played a less decisive role. In support, the interaction between KAM and group was only found at the lateral plateau, which is the most common site of bone marrow lesion and fractures with cortical discontinuity following ACL injury 32,33 . Loading distribution during gait, which KAM serves as a proxy, maybe more important in OA progression at the lateral plateau in patients with non-traumatic knee OA.…”
Section: Discussionmentioning
confidence: 81%
“…Preoperative ROM deficits are associated with higher rates of arthrofibrosis 36 and lower subjective scores. 43 Driban et al 12 also found that increased bone bruise volume is associated with lower Knee injury and Osteoarthritis Outcome Score (KOOS) pain scores in the absence of a depression fracture. When depression fractures were present, this relationship was nonexistent.…”
Section: Clinical Outcomesmentioning
confidence: 97%
“…Recent studies into the distribution of bone bruises within the knee found a wide range: between 48.3% and 91.7% of ACL tears had a bruise of the lateral femoral condyle (LFC) (Figure 1), 1,5,7,8,12,26,27,31,35,44,46 between 49.4% and 97.6% of the lateral tibial plateau (LTP) (Figure 1), 1,5,7,8,12,26,27,31,35,44,46 between 12.5% and 53% of the medial femoral condyle (MFC) (Figure 2), 1,7,8,12,26,27,44,46 and between 12.4% and 83.5% of the medial tibial plateau (MTP) (Figure 3). 1,7,8,12,26,27,31,44,46…”
Section: Mechanisms Of Bone Bruisesmentioning
confidence: 99%
See 1 more Smart Citation